Socio-Economic Resilience of Oil Palm Farmers in Facing Fluctuations in Oil Palm Fruit Selling Prices in Mahahe Village - Abd. Latif; Firdaus W. Suhaeb; Ashari Ismail (Journal of Social Science and Economics (JOSSE), 2025)
This study aims to analyze: (1) the factors influencing the resilience of oil palm farmers in facing fluctuations in fresh fruit bunch (FFB) prices in Mahahe Village, Central Mamuju Regency, and (2) the forms of resilience demonstrated by oil palm farmers under such conditions. This research employs a qualitative approach with a descriptive method. Ten informants were selected based on specific criteria using a purposive sampling technique. Data were collected through observation, interviews, and documentation, while data validity was ensured through source triangulation. The findings indicate that: (1) the factors influencing the resilience of oil palm farmers against FFB price fluctuations in Mahahe Village include (a) self-esteem, (b) social support, (c) spirituality or religiosity, and (d) positive emotions. (2) The forms of resilience displayed by oil palm farmers in response to price fluctuations are categorized into two types: (a) overcoming the odds (managing challenges and difficulties) through income diversification strategies or seeking alternative employment outside the agricultural sector, and (b) coping (managing anxiety and stress) by engaging in alternative activities such as fishing, livestock raising, praying, exercising, and enjoying the tranquility of working in the plantation